The Role of Notaries in The Limited Liability Company Registration Process Through Online Ahu Services in Tegal Regency - Algusti, Muhamad Gemas; Setyawati, Setyawati (Jurnal Konstatering, 2025)
This study aims to analyze the role of notaries in the process of registering Limited Liability Companies (PT) through the AHU Online system in Tegal Regency, as well as to identify obstacles and solutions faced in its implementation. This study uses a juridical-empirical approach with legal analysis and field data. The sociological juridical approach is applied to understand the relationship between law and social conditions, as well as the challenges faced by notaries. Primary data were obtained from interviews with notaries, while secondary data were collected from legal sources and related literature. Qualitative analysis was used to describe the phenomenon and understand the role and responsibilities of notaries in technology-based PT registration. The results of the study indicate that notaries have a crucial role in ensuring legal certainty in PT registration through the AHU Online system, despite facing internal and external obstacles. The obstacles found include a lack of understanding of the system, technical problems, and a lack of technical support. This study recommends increased training, improvements in technological infrastructure, and closer collaboration between notaries, AHU managers, and the government to improve efficiency and quality of service.